Symposium 13: The Metaphor of Networks in Learning: Communities, Collaboration and Practice - Jones, Chris; Esnault, Liliane (Proceedings of the International Conference on Networked Learning, 2004)
This paper explores the use of the network metaphor and the way in which it relates to Computer Supported Collaborative Learning (CSCL) and Communities of Practice. The idea of networked learning stresses the interaction of learners, tutors and their resources through networks. The arguments put in this article are firstly that learning technology needs to take account of the wider debate about networks and secondly that research in this field needs to address the theoretical and practical issues raised by advances in the field of networks. A further argument made is that the idea of the network can act as a unifying concept allowing us to bring together apparently disparate elements in the field of e-learning.